Effects of carboxymethyl cellulose on the emulsifying, gel and digestive properties of myofibrillar protein-soybean oil emulsion. (1st June 2023) - Zhou, Lei; Jiang, Jinyuan; Feng, Fan; Wang, Jingyu; Cai, Jiaming; Xing, Lujuan; Zhou, Guanghong; Zhang, Wangang
Abstract: Improving the qualities of vegetable oil replaced animal fat meat products is particularly fascinating for the development of healthy meat products. This work was designed to investigate the effects of different carboxymethyl cellulose (CMC) concentrations (0.01 %, 0.05 %, 0.1 %, 0.2 %, and 0.5 %) on the emulsifying, gelation, and digestive properties of myofibrillar protein (MP)-soybean oil emulsions. The changes in MP emulsion characteristics, gelation properties, protein digestibility, and oil release rate were determined. Results demonstrated that CMC addition decreased the average droplet size and increased the apparent viscosity, storage modulus, and loss modulus of MP emulsions, and a 0.5 % CMC addition significantly increased the storage stability during 6 weeks. Lower CMC addition (0.01 % to 0.1 %) increased the hardness, chewiness, and gumminess of emulsion gel especially for the 0.1 % CMC addition, while higher CMC (0.5 %) content decreased the texture properties and water holding capacity of emulsion gels. The addition of CMC decreased protein digestibility during the gastric stage, and 0.01 % and 0.05 % CMC addition significantly decreased the free fatty acid release rate. In summary, the addition of CMC could improve the stability of MP emulsion and the texture properties of the emulsion gels, and decrease protein digestibility during the gastric stage. Graphical abstract: Unlabelled Image